P213 Positive drivers and potential barriers to implementation of hospital at home selected by low risk decaf score. (15th November 2016) - Dismore, L; Echevarria, C; Van-Wersch, A; Simpson, AJ; Gibson, GJ; Bourke, SC
Abstract : Background: Despite endorsement in guidelines, many hospitals do not offer hospital at home (HAH) for COPD exacerbation (AECOPD), partly reflecting the previous lack of a robust prognostic score to guide selection. The DECAF score addresses this concern, and should be routinely scored on admission. 1 In a RCT we have shown that HAH selected by DECAF score 0–1 is safe and effective. Up to 50% of admitted patients are suitable. Our population included patients with higher medical dependency than earlier trials and HAH was supported by 24/7 specialist on-call. In an embedded qualitative study, we identified positive drivers for, and potential barriers to, use of HAH to inform service implementation. Methods: Patients, carers, clinicians and managers were purposely selected to ensure diversity. Semi-structured interviews were conducted and Thematic-Construct Analysis employed. 2 Results: 44 patients (HAH/inpatient care/declined randomisation), 15 carers, 14 consultants, 11 specialist nurses and 4 managers were interviewed. ' Positive drivers' were divided into two sub-constructs: 'Feeling more at ease and comfortable in own home environment'; and 'Feeling safe, reassured and appreciated through continuity of hospital care'. Positive influences on independence, perceived rate of recovery, sleep quality, mood and contact with friends and family were noted. At 14 days post-presentation, 90% of patients stated they would prefer HAH over inpatient care for subsequent exacerbations of similar severity. Counter-intuitively, carers reported greater convenience rather than increased burden. 'Potential Barriers' were grouped into two sub-constructs: 'Personal preferences'; and 'Resistance to change'. Some patients highlighted fear of being alone at night and dislike of strangers visiting their home; nurses cited higher workload and greater responsibility (with experience, viewed positively); whilst operational concerns included keeping medical records in a patient's home and inability to capture activity within current payment systems. Conclusions: HAH selected by DECAF allows the inclusion of more patients than existing models, and is preferred to inpatient care by most patients and their families. During the trial few barriers to implementation were identified, and were effectively overcome. Hospitals planning to implement HAH selected by DECAF should pre-emptively address these issues. References: National COPD Audit Report, 2015. Dismore. J Health psychol, 2016.